PEREMPUAN DUNIA KETIGA DALAM ANTOLOGI CERITA PENDEK “KETIKA SAATNYA” - Ramis Rauf; Afriani Ulya (TELAGA BAHASA, 2021)
The aim of this study was to reveal the phenomenon of socio-cultural facts of women as subalterns in the anthology of the short story "Ketika Saatnya" by Darmawati Majid. The problem in this research was "how were the third-world women narrated in the anthology of short stories Ketika Saatnya?" This study used the subalternate theory by Gayatri Chakravorty Spivak. The term subaltern referred to a population that was socially, politically, and geographically subdued by a group that controls them. The subaltern was a group whose voice was always represented and became a tool of a hegemonic practice that symbolized political, military, social, and even cultural domination by one group over another. The results of this study revealed that the position of women as subalterns was narrated as a subaltern group trying to convey their voice to be heard even though they occupied a position as "third-world women" who were trapped between tradition and modernization.